Grupo Clamor e projeto Brasil nunca mais na defesa dos direitos humanos - Oliveira, Fernando da Silva (2022)
Between 1964 and 1985, the National Security Doctrine (DSN) established a civil-military dictatorship in Brazil through a coup that took power by storm. Equipped with its security organs, the dictatorship kidnapped, tortured and disappeared with hundreds of Brazilians. As a reaction, the group Clamor was born in 1978. Almost at the same time, the urgency arises to safeguard the military processes that the dictatorship maintained in the Superior Military Court (STM) in Brasília. A team formed by people imbued with solidarity formed the project Brazil: Never Again (PBNM) in mid-1979. Copies of these processes proved the crimes committed by the dictatorship. Twenty-three years later, another PBNM team took on the mission of guaranteeing the project's existence. The three teams we've addressed take the place of non-repetition and transitional justice devices.